Pharmacovigilance Study of Antidiabetic Drugs in Diabetes Mellitus Patients in Three Pharmacies in Yogyakarta - Urfiyya, Qarriy 'Aina; Kamilabanat, Ratu Aimeesadra; Solekhah, Rahma Febita (Faculty of Pharmacy, Universitas Gadjah Mada, 2025)
Background: Diabetes mellitus has become a global health problem. Indonesia has the third highest number of diabetes mellitus cases in the Southeast Asia region, with a prevalence of 11.3%. The high prevalence of diabetes mellitus increases the risk of Adverse Drug Reaction (ADR). Pharmacovigilance studies are important to detect possible adverse drug reaction of antidiabetic drugs.Objective: This study aimed to describe and analyze the adverse drug reaction of using antidiabetic drugs at three pharmacies in Yogyakarta City.Methods: This study used an analytic observational with a cross-sectional study design. Data were collected at three pharmacies in Yogyakarta City from 59 patients with diabetes mellitus who met the inclusion and exclusion criteria. The instrument used was an interview guide that refers to the Naranjo form. Data analysis included the incidence of adverse drug reaction according to patient characteristics, type of therapy, and description of antidiabetic adverse drug reaction based on causality.Results: The results showed that antidiabetic ADRs occurred in 19 patients (32%). The incidence of ADRs was 68% in men and 32% in women. The incidence of adverse drug reaction was most prevalent at the age of 56-65 years (47%). The most common adverse drug reaction of antidiabetic metformin was flatulence, drowsiness, decreased appetite and dyspepsia, diarrhea, weight loss and nausea and vomiting.Conclusion: This study concluded that the most common ADRs of antidiabetics was the probable and possible category (42%). The most common cause of ADRs was metformin (53%).